P-44 Myositis ossificans traumatica: a consequence of an early return to training?. (18th November 2016) - Martins, Úrsula; Cunha, João; Silva, Joana; Sousa, Pedro; Gomes, Joana; Branco, Catarina Aguiar
Abstract : Myositis ossificans (MO) is a condition characterised by non-neoplastic heterotopic proliferation of bone in soft tissue and skeletal muscle. It is benign and usually self-limited. The traumatic form is the most common, corresponding to 60-75% of cases, and occurs as a complication of large haematomas (20% of them). In athletes, causes of MO are contusions, strains or repeated micro-injuries by overuse. The bone will usually grow 2 to 4 weeks after the injury and becomes mature within 3 to 6 months. Symptoms of MO include pain in the muscle, and a restricted range of motion(ROM), particularly if the ossification occurs near a joint. An X-ray can confirm the diagnosis. Resolution with conservative treatment is seen in almost all cases, despite heterotrophic bone exostosis. Whenever a painful mass persists, surgical excision can be considered. J.C., 18-year-old female, gymnast of a national team, who practices 25 hours per week. Two weeks before the World Championship, after an intense training session, she developed an exuberant swelling on the cubital fossa and brachial region, restricted ROM (loss of 70° on elbow extension), without history of trauma during that session. Magnetic resonance imaging (MRI) demonstrated an increased volume of the brachial muscle body, with interstitial oedema, and an area corresponding to an intramuscular haematoma measuring 4 cm long and 1.4 cm thick, with changes suggesting interstitial partial rupture. Haematoma aspiration was not performed, no NSAIDs were given and she started a 3 day rehabilitation program that included immobilisation of the muscles in slight tension with compression, ice and elevation. Thereafter, manual therapy, stretching, strengthening (progressive eccentric training) and proprioceptive retraining were done, with gym routine to maintain flexibility, strength and aerobic conditioning. 15days after the lesion, she competed in the World Championship, although still having a 10° restriction on elbow extension and a painful isometric contraction of brachial muscle (Figure 1) After the competition, she re-started the previous rehabilitation program, with progressive complexity evolution during 30days. 45days after the lesion, the athlete recovered full range of motion, normal muscle function, returning to her previous gymnastic activity without pain, but a large mass still remained in the brachial muscle. Ultrasound and MRI revealed a MO of brachial muscle measuring 2.3cm transverse, 2.5cm anteroposterior and 6cm longitudinal diameter (Fig 2). As she had no functional limitations or pain, she continued to train and started conservative treatment of MO with extracorporeal-shock-wave-therapy(ESWT) and a program of supervised exercises and stretching. MO is a condition related to some risk factors, such as the severity of the initial injury, localised tenderness and swelling, re-injury during the recovery, delay in treatment over 72hours, improper management of the muscle haematoma, precocious return to competition. In this specific clinical case, the aspiration of the haematoma was not performed. Despite the correct approach of the injury, the athlete returned to activity too early, which may have contributed to the development of MO. If MO develops, the graded restoration of flexibility and strength with minimal pain becomes the goal of rehabilitation.